2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6655390
|View full text |Cite
|
Sign up to set email alerts
|

On the exploitation of OFDMA properties for an efficient alert message flooding in VANETs

Abstract: Vehicular ad hoc networks (VANETs) drive new challenging research issues at different layers of the protocol pillar, from physical to application. Focusing on the medium access layer, one of the most promising and not yet fully explored option is the adoption of orthogonal frequency division multiple access (OFDMA). Besides guaranteeing high spectral efficiency and effective resource allocation, it relies at the physical layer on orthogonal frequency division multiplexing, which allows repetitions of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To increase reliability and resource usage efficiency based on medium access control (MAC) protocol, Bazzi et al [12,13], suggested applying orthogonal frequency division multiple access (OFDMA) for alert message flooding in VANETs. They compared their protocols with other benchmark MAC protocols.…”
Section: Introductionmentioning
confidence: 99%
“…To increase reliability and resource usage efficiency based on medium access control (MAC) protocol, Bazzi et al [12,13], suggested applying orthogonal frequency division multiple access (OFDMA) for alert message flooding in VANETs. They compared their protocols with other benchmark MAC protocols.…”
Section: Introductionmentioning
confidence: 99%